(2-{ 1,1-Bis(hydroxymethyl)-2-oxidoethyl iminomethyl}-4-chlorophenolato- kappa O-3,N,O ')dibutyltin(IV) - Lee, S.M.; Lo, K.M.; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
In the title compound, [Sn(C4H9)2(C11H12BrNO4)], the Schiff base ligand chelates to the SnIV atom through the two deprotonated hydroxy groups, as well as through the N atom, to confer an overall cis-C2SnNO2 trigonal-bipyramidal geometry at the SnIV atom [C-Sn-C = 129.92 (9)°]. The remaining methylenehydroxy groups engage in O-H...O hydrogen bonding with the O atoms of adjacent molecules, leading to infinite supramolecular chains propagating in [001].